Auditory Beat Stimulation and its Effects on Cognition and Mood States - Chaieb, Leila; Wilpert, Elke Caroline; Reber, Thomas P.; Fell, Juergen (Frontiers in Psychiatry, 2015)
Auditory beat stimulation may be a promising new tool for the manipulation of cognitive processes and the modulation of mood-states. Here we aim to review the literature examining the most current applications of auditory beat stimulation and its targets. We give a brief overview of research on auditory steady-state responses and its relationship to auditory beat stimulation. We have summarized relevant studies investigating the neurophysiological changes related to auditory beat stimulation and how they impact upon the design of appropriate stimulation protocols. Focusing on binaural beat stimulation, we then discuss the role of monaural and binaural beat frequencies in cognition and mood-states, in addition to their efficacy in targeting disease symptoms. We aim to highlight important points concerning stimulation parameters and try to address why there are often contradictory findings with regard to the outcomes of auditory beat stimulation.